Translating General Game Descriptions into an Action Language - Thielscher, Michael (Logic Programming, Knowledge Representation, and Nonmonotonic Reasoning, 2011)
The game description language (GDL), which is the basis for the grand AI challenge of general game playing, can be viewed as yet another action language. However, due to its unique way of addressing the frame problem, GDL turned out to be surprisingly difficult to relate to any of the classical action formalisms. In this paper, we present the first complete embedding of GDL into an existing member, known as, $\cal C\!$ +, of the family of action languages. Our provably correct translation paves the way for applying known results from reasoning about actions, including competitive implementations such as the Causal Calculator, to the new and ambitious challenge of general game playing.